Pricing and investment in public enterprise (New Delhi, 1974)
This voulme included the deliberations of the Seminars held by the Institute of Public Enterpris in Bangalore in September 1969 and in New Delhi in January 1970, along with the working papers, on pricing and Investment in Public Enterprise- subjects of fundamental importance. The Director of Institute of Public Enterprise and General Editor thanks all persons and institutions that contributed to the success of the Seminars.
Keywords: Government business enterprises finance